Research progress on the cannabinoid type-2 receptor and Parkinson’s disease - Yu, Xiaoqi; Jia, Yi; Dong, Yuan (Frontiers in Aging Neuroscience, 2024)
Parkinson's disease (PD) is featured by movement impairments, including tremors, bradykinesia, muscle stiffness, and imbalance. PD is also associated with many nonmotor symptoms, such as cognitive impairments, dementia, and mental disorders.Previous studies identify the associations between PD progression and factors such as α-synuclein aggregation, mitochondrial dysfunction, inflammation, and cell death. The cannabinoid type-2 receptor (CB2 receptor) is a transmembrane G-protein-coupled receptor and has been extensively studied as part of the endocannabinoid system. CB2 receptor is recently emerged as a promising target for anti-inflammatory treatment for neurodegenerative diseases. It is reported to modulate mitochondrial function, oxidative stress, iron transport, and neuroinflammation that contribute to neuronal cell death. Additionally, CB2 receptor possesses the potential to provide feedback on electrophysiological processes, offering new possibilities for PD treatment. This review summarized the mechanisms underlying PD pathogenesis. We also discussed the potential regulatory role played by CB2 receptor in PD.